2017
DOI: 10.1145/3068772
|View full text |Cite
|
Sign up to set email alerts
|

Fast and powerful hashing using tabulation

Abstract: Randomized algorithms are often enjoyed for their simplicity, but the hash functions employed to yield the desired probabilistic guarantees are often too complicated to be practical. Here we survey recent results on how simple hashing schemes based on tabulation provide unexpectedly strong guarantees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…A separate hash function is used for each row of the CMS with a range equal to the range of columns. In this work, we use tabulation hashing [18] which has been recently analyzed by Patrascu and Thorup et al [13,16] and shown to provide strong statistical guarantees despite of its simplicity. Furthermore, it is even as fast as the classic multiply-mod-prime scheme, i.e., ( + ) mod .…”
Section: Notation and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate hash function is used for each row of the CMS with a range equal to the range of columns. In this work, we use tabulation hashing [18] which has been recently analyzed by Patrascu and Thorup et al [13,16] and shown to provide strong statistical guarantees despite of its simplicity. Furthermore, it is even as fast as the classic multiply-mod-prime scheme, i.e., ( + ) mod .…”
Section: Notation and Backgroundmentioning
confidence: 99%
“…Assuming each element in  is represented in 32 bits (the hash function can also be used to hash 64-bit stream items [16]) and the desired output is also 32 bits, tabulation hashing works as follows: rst a 4×256 table is generated and lled with random 32-bit values. Given a 32-bit input , each character, i.e., 8-bit value, of is used as an index for the corresponding row.…”
Section: Notation and Backgroundmentioning
confidence: 99%
“…We sample a MinHash function h by sampling a random Zobrist hash function g and let h(x) = argmin j∈x g(j). Zobrist hashing (also known as simple tabulation hashing) has been shown theoretically to have strong MinHash properties and is very fast in practice [27], [28]. We set t = 128 in our experiments, see discussion later.…”
Section: A Chosen Path Similarity Joinmentioning
confidence: 99%
“…Linear Probing or Progressive Overflow is a classic implementation of the hash table. It uses the hash h function to map a set of n keys into an m size array [13]. In the Po method, if the kay is crashd then the kay value wil be placed on the next index that is still empaty.…”
Section: Progressive Overflowmentioning
confidence: 99%